Intimate Femicide-Suicide in Italy Between 2015 and 2019: A Comparison to Intimate Femicide Without Suicide - Solinas-Saunders, Monica (Homicide studies, 2024)
The study compares incidents of intimate femicide-suicide (IFS) to incidents of intimate femicide without suicide (IFWS) that occurred in Italy between 2015 and 2019 and examines the influence of situational, sociocultural, and individual characteristics. Findings from the multivariate analysis show that incidents of IFS are more likely than incidents of IFWS to involve the use of firearms and the death of multiple victims. Furthermore, incidents of IFS are less likely than incidents of IFWS to involve previous instances of domestic violence and less likely to involve a perpetrator who was unemployed at the time of the incident.